Greenwashing behaviours of selected automotive companies in the Czech Republic - Vančurová, Šárka; Chocholáč, Jan (Melandrium, 2022)
Green marketing and the use of green marketing communication is very popular nowadays, not only with companies because it responds to the trend of sustainability and corporate social responsibility. Green marketing communication is classified as an innovative management tactics. It also positively influences the perception of the company, brand and products by customers and consumers. On the other hand, it is possible to move from green marketing communication to greenwashing that is defined as any misinformation spread by an organisation to present an environmentally responsible public image of itself. The automotive sector is a very suitable sector for the use of green marketing communication but on the other hand also for greenwashing. This article focuses on the greenwashing behaviour of selected automotive companies in the Czech Republic that produce passenger cars. The aim of the article is to identify and analyse examples of greenwashing behaviour in selected automotive companies in the Czech Republic that produce passenger cars. The article contains a theoretical definition of the greenwashing concept and greenwashing tactics. The analysis of greenwashing behaviour is conducted using qualitative content analysis and comparative analysis. The results are discussed in the context of other related studies.
Greenwashing vybraných automobilových společností v České republice
Keywords: sustainability; green marketing; greenwashing practices; consumer perceptions; automotive industry; udržitelnost; zelený marketing; praktiky greenwashingu; vnímání spotřebitelů; automobilový průmysl